Fatigue Performance of Laser Additive Manufactured Ti–6Al–4V in Very High Cycle Fatigue Regime up to 109 Cycles - Wycisk, Eric; Siddique, Shafaqat; Herzog, Dirk; Walther, Frank; Emmelmann, Claus (Frontiers in Materials, 2015)
Additive manufacturing technologies are in the process of establishing themselves as an alternative production technology to conventional manufacturing such as casting or milling. Especially laser additive manufacturing (LAM) enables the production of metallic parts with mechanical properties comparable to conventionally manufactured components. Due to the high geometrical freedom in LAM the technology enables the production of ultra-light weight designs and therefore gains increasing importance in aircraft and space industry. The high quality standards of these industries demand predictability of material properties for static and dynamic load cases. However, fatigue properties especially in the very high cycle fatigue regime until 109 cycles have not been sufficiently determined yet. Therefore this paper presents an analysis of fatigue properties of laser additive manufactured Ti-6Al-4V under cyclic tension-tension until 107 cycles and tension-compression load until 109 cycles. For the analysis of laser additive manufactured titanium alloy Ti-6Al-4V Woehler fatigue tests under tension-tension and tension-compression were carried out in the high cycle and very high cycle fatigue regime. Specimens in stress-relieved as well as hot-isostatic-pressed conditions were analyzed regarding crack initiation site, mean stress sensitivity and overall fatigue performance. The determined fatigue properties show values in the range of conventionally manufactured Ti-6Al-4V with particularly good performance for hot-isostatic-pressed additive-manufactured material. For all conditions the results show no conventional fatigue limit but a constant increase in fatigue life with decreasing loads. No effects of test frequency on life span could be determined. However, independently of testing principle, a shift of crack initiation from surface to internal initiation could be observed with increasing cycles to failure.